1987
DOI: 10.1002/cm.970080208
|View full text |Cite
|
Sign up to set email alerts
|

Cell type‐specific association between two types of spectrin and two types of intermediate filaments

Abstract: We have demonstrated a differential association between two types of spectrin, from erythrocytes and brain, with two types of intermediate filaments, vimentin filaments and neurofilaments. Electron microscopy showed that erythrocyte spectrin promoted the binding of vimentin filaments to red cell inside-out vesicles via lateral associations with the filaments. In vitro binding studies showed that the association of spectrin with vimentin filaments was apparently saturable, increased with temperature, and could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…We found that βII spectrin immunoreactivity was detected like 4.1B all along the internodal axolemma in sciatic nerve, whereas this cortical enrichment was altered in the absence of 4.1B. βII spectrin can associate with neurofilaments and may promote the association of intermediate filaments with the plasma membrane and contribute to the organization of neurofilaments [47][49]. Since neurofilaments control axonal radial growth with their subunit composition playing a crucial role in determining normal axonal calibers [50], 4.1B might control axonal caliber by controlling intermediate filaments organization through its association with βII spectrin.…”
Section: Discussionmentioning
confidence: 77%
“…We found that βII spectrin immunoreactivity was detected like 4.1B all along the internodal axolemma in sciatic nerve, whereas this cortical enrichment was altered in the absence of 4.1B. βII spectrin can associate with neurofilaments and may promote the association of intermediate filaments with the plasma membrane and contribute to the organization of neurofilaments [47][49]. Since neurofilaments control axonal radial growth with their subunit composition playing a crucial role in determining normal axonal calibers [50], 4.1B might control axonal caliber by controlling intermediate filaments organization through its association with βII spectrin.…”
Section: Discussionmentioning
confidence: 77%
“…Several candidate proteins that may be involved in the interaction with phospho-ser52 K18 include desmoplakin (DP), fodrin, or other cell surface associated proteins such as integrins. Although to our knowledge a fodrin-keratin interaction has not been described, such an interaction would not be surprising given the polarized distribution of fodrin in epithelial cells (reviewed by Bennett and Gilligan, 1993), and the described association between fodrin and other IF proteins including vimentin (Mangeat and Burridge, 1984), NF (Frappier et al, 1987;Langley and Cohen, 1987), and peripherin (Takemura et al, 1993). In addition, cell surface associated receptors could also potentially interact with the phospho-ser52 K18.…”
Section: Potential Implications For the Polarity Of Distribution Of Pmentioning
confidence: 86%
“…This suggests that, unlike desmin, which not only interacts with the sarcolemma at Z line domains but also surrounds the Z disks throughout the myoplasm, cytokeratins may interact preferentially with the sarcolemma. Because other members of the IF superfamily can bind to ␤-spectrins (Langley and Cohen, 1987;Frappier et al, 1992aFrappier et al, , 1992bMacioce et al, 1999), cytokeratin-sarcolemmal interactions may even be mediated Figure 9. Model of the sarcolemmal membrane skeleton and its relationship to desmin and cytokeratin.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is tempting to speculate that desmin IFs anchor to ␣-fodrin at the sarcolemma at Z line domains, binding of desmin to ␣ subunits of the spectrin superfamily has yet to be reported. Desmin and other IF proteins bind to spectrin and to ankyrin (Georgatos and Blobel, 1987;Langley and Cohen, 1987;Frappier et al, 1991Frappier et al, , 1992Macioce et al, 1999), however, so anchoring of desmin IFs to the sarcolemma may be mediated by the ␣␤-spectrin heteromers and ankyrin that are present at Z line domains (Porter et al, 1997;Williams and Bloch, 1999b;Williams et al, 2001; see Figure 9). …”
Section: Discussionmentioning
confidence: 99%